2019
DOI: 10.1083/jcb.201905026
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint signaling and error correction require regulation of the MPS1 T-loop by PP2A-B56

Abstract: Supplemental Figure legendsFigure S1. MPS1 autophosphorylation and localisation are regulated by PP2A-B56. (A) Control depleted or MPS1-depleted HeLa MPS1-GFP mitotic cells were treated with MPS1 inhibitor or DMSO for 5 min as indicated. Cells were stained with antibodies against MPS1 pT676 and CENP-C. Total MPS1-GFP was detected by GFP fluorescence. (B) Recombinant, insect cell expressed wild type (WT) or kinasedead (KD) His-MPS1 was treated with l-phosphatase or reaction buffer alone and analysed by SDS-PAGE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…Furthermore, this may be reinforced by an additional positive feedback loop to MPS1 itself, since PLK1 can phosphorylate the activation loop of MPS1 to stimulate its kinase activity 26,27,37 (MPS1→BUB:PLK1→MPS1, Figure 4B, P2). This may help to explain the recent observation that this 'autoactivation' site remains phosphorylated when MPS1 is inhibited in BUBR1 PP2A cells 38 . In this case, PP2A removal may increase phosphorylation indirectly via PLK1, instead of (or in addition to) preventing dephosphorylation directly, as the authors propose.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, this may be reinforced by an additional positive feedback loop to MPS1 itself, since PLK1 can phosphorylate the activation loop of MPS1 to stimulate its kinase activity 26,27,37 (MPS1→BUB:PLK1→MPS1, Figure 4B, P2). This may help to explain the recent observation that this 'autoactivation' site remains phosphorylated when MPS1 is inhibited in BUBR1 PP2A cells 38 . In this case, PP2A removal may increase phosphorylation indirectly via PLK1, instead of (or in addition to) preventing dephosphorylation directly, as the authors propose.…”
Section: Discussionmentioning
confidence: 78%
“…To test whether PP1 activity contributes to the accelerated destruction of cyclin B1 we performed a biochemical analysis of mitotic exit in the presence of the highly specific small molecule PP1 inhibitor tautomycetin which inhibits all three PP1 isoforms but not PP2A (Choy et al, 2017;Hayward et al, 2019c). Tautomycetin prevented dephosphorylation of PPP1CA-pT320 ( Figure 1A and 1B), and the half-life of pT320 increased from ~2 min in the control to >60 min ( Figure 1C).…”
Section: Pp1 Contributes To Activation Of Apc/c During Mitotic Exitmentioning
confidence: 99%
“…CDC20 was depleted using siRNA oligo #14 5'-CGGAAGACCUGCCGUUACA-3' (ThermoFisher). siRNA oligos for PP2A-B55 and PP2A-B56 have been described (Hayward et al, 2019a;Hayward et al, 2019c).…”
Section: Molecular Biology and Sirna Reagentsmentioning
confidence: 99%
“…However, it has also recently been shown that Mad1 stably interacts with Cdk1 and that Mps1, through kinetochore recruitment of Mad1, in turn, promotes kinetochore localization of Cdk1 (Figure 2) 72,73 . At kinetochores, Cdk1 may further phosphorylate other substrates to sustain the SAC like Cdc20 or BubR1 and possibly also help error correction and SAC resolution by favoring BubR1 interaction with the protein phosphatase PP2A-B56 65, [78][79][80] . Recent evidence also indicated how the indirect downregulation of the protein phosphatase PP2A-B55 activity by Cdk1 is instrumental for the SAC-promoting action of Cdk1 itself 72,81 .…”
Section: Cdk1 and The Sacmentioning
confidence: 99%